2003
DOI: 10.1002/cncr.11214
|View full text |Cite
|
Sign up to set email alerts
|

Lung carcinoma after radiation therapy in women treated with lumpectomy or mastectomy for primary breast carcinoma

Abstract: BACKGROUNDPrior studies have demonstrated that women who receive adjuvant radiation therapy (RT) after mastectomy for breast carcinoma have an increased risk of a second primary lung carcinoma after 10 years, but, to the authors' knowledge, the risk associated with adjuvant RT after breast‐conserving surgery (lumpectomy) has yet to be determined. The purpose of the current study was to confirm and extend earlier findings of the effects of postmastectomy RT on second primary lung carcinoma and to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
76
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(84 citation statements)
references
References 25 publications
5
76
1
2
Order By: Relevance
“…17 Although direct comparisons are complicated by the lack of information on background risk in the populations included in our study, our results (relative risk estimates in the order of 1.5-2.0) suggest a greater risk than those based on ICRP estimates. Similar conclusions are reached when comparing our results with the relative risk estimates from the studies of atomic bomb survivors 2 and patients treated with radiotherapy, [18][19][20] which are the main basis for the ICRP estimates. These considerations lend credibility to the hypothesis that our results are, at least in part, due to reporting bias or residual confounding.…”
Section: Discussionsupporting
confidence: 83%
“…17 Although direct comparisons are complicated by the lack of information on background risk in the populations included in our study, our results (relative risk estimates in the order of 1.5-2.0) suggest a greater risk than those based on ICRP estimates. Similar conclusions are reached when comparing our results with the relative risk estimates from the studies of atomic bomb survivors 2 and patients treated with radiotherapy, [18][19][20] which are the main basis for the ICRP estimates. These considerations lend credibility to the hypothesis that our results are, at least in part, due to reporting bias or residual confounding.…”
Section: Discussionsupporting
confidence: 83%
“…Our site-specific results were broadly similar to those from a pooled analysis of 63 randomised clinical trials of breast cancer radiotherapy and several observational studies. In these studies, there was evidence of increased risks of lung (Zablotska and Neugut, 2003;Roychoudhuri et al, 2004;Clarke et al, 2005;Darby et al, 2005;Andersson et al, 2008;Schaapveld et al, 2008), oesophageal (Zablotska and Neugut, 2003;Roychoudhuri et al, 2004;Clarke et al, 2005) and contralateral breast cancer (Gao et al, 2003;Roychoudhuri et al, 2004;Clarke et al, 2005), as well as soft tissue sarcomas (Huang and Mackillop, 2001;Clarke et al, 2005;Andersson et al, 2008), in women treated with radiotherapy compared with unirradiated women. In the pooled analysis of clinical trials , the authors did not estimate attributable risks, but it was possible to estimate them on the basis of the data presented.…”
Section: Discussionmentioning
confidence: 99%
“…Shared environmental and genetic factors are likely to be involved, but some of the increased risk is probably a late adverse effect from the cancer treatments such as radiotherapy . Randomised trials and cancer registry-based studies have shown that radiotherapy significantly reduces the risk of recurrence and breast cancer mortality, and also increases the risk of second cancers of the lung, oesophagus, soft tissue, contralateral breast and leukaemia (Huang and Mackillop, 2001;Gao et al, 2003;Zablotska and Neugut, 2003;Clarke et al, 2005;Zablotska et al, 2005).…”
mentioning
confidence: 99%
“…The overall survival rate of patients with early advanced breast cancer (BC) has increased over the years largely because adjuvant therapy, whether chemotherapy, radiotherapy or hormone therapy, has helped prevent local and distant failures (Fox, 1979;Jones and Raghavan, 1993; EBCTCG, 2005). Second malignancies that occur in long-term survivors may be due to sporadic cancers that would have occurred anyway, environmental or genetic factors (Klijn et al, 1997;Schrag et al, 1997;Turner et al, 1999;Meijers-Heijboer et al, 2000;Pierce et al, 2000Pierce et al, , 2003 StoppaLyonnet et al, 2000;Galper et al, 2002;Kauff et al, 2002;Pierce, 2002;Robson, 2002;Seynaeve et al, 2004; Kirova et al, 2005aKirova et al, , b, 2006aLaki et al, 2007), or BC treatment (Neugut et al, 1993;Inskip et al, 1994;Ahsan and Neugut, 1998;Karlsson et al, 1998;Kirova et al, 1998 Kirova et al, , 2005aKirova et al, , b, 2007Obedian et al, 2000;Rubino et al, 2000;Scholl et al, 2001;Shousha et al 2001;Yap et al, 2002 Yap et al, , 2005Deutsch et al, 2003;Zablotska and Neugut, 2003;Zablotska et al, 2005;Mellemkjaer et al, 2006) The aim of this study was to estimate the risk of a second malignancy after adjuvant treatment for BC in a homogeneous cohort of patients from a single institution. The observed incidence of second malignancies in these BC patients was compared with the expected age-adjusted number of new cases in the general population of French women as given by data from five regional registries (Remontet et al, 2003).…”
mentioning
confidence: 99%